DANA TALANGAN HAJI DALAM ETIKA ISLAM - Aye Sudarto (Multazam : Jurnal Manajemen Haji dan Umrah, 2021)
It is inappropriate for people to be trapped in products containing elements of usury which result in imperfection of the pilgrimage because they depart in a way that contains elements of gharar. The practice opens the door to danger, and brings harm. The Ministry of Religion which has the authority to evaluate the existence of hajj bailout funds with the Regulation of the Minister of Religion (PMA) RI No. 24 of 2016. The Hajj bailout fund is intended to meet the customer's lack of funds in meeting the minimum requirements to get the Hajj portion. This program is enough to ease the people in preparing for the departure of the pilgrimage. For LKS, this program is also a benefit where LKS gets Ujrah from every customer who participates in the Hajj bailout program. On the other hand, the bailout program creates and contains disadvantages that are not in accordance with Islamic ethics. Hajj bailouts incur debts that can cause damage to the purity of the pilgrimage. The Hajj bailout financing contract at LKS attracts ujrah based on the time and amount of the bailout fund. This practice is not in accordance with the DSN-MUI Fatwa No. 29 of 2002. The hajj bailout has an effect on the length and length of the waiting list for hajj departures.